PLANT-BASED BIOPLASTICS AND AN ECO-FRIENDLY ALTERNATIVE TO CONVENTIONAL PLASTICS - Dr Sushama Sukhdev Kadam,; Dr. (MRS.) SOSANNA LAL,; Dr. Ram Babu,; Dr.Mukti Verma,; Dr Shobha Thakur,; Dr Aruna Kumari Nakkella, (The Bioscan, 2025)
The increasing environmental burden of petroleum-based plastics has intensified the global search for sustainable alternatives. The widespread use of conventional plastics has led to severe ecological challenges, including excessive plastic waste, microplastic pollution, and greenhouse gas emissions, contributing to climate change. One promising solution is the development of plant-based bioplastics, which offer renewable, biodegradable, and eco-friendly characteristics compared to traditional plastics derived from fossil fuels. These bioplastics are synthesized from plant-based sources such as corn starch, sugarcane, cassava, cellulose, and algae, making them a viable alternative for packaging, agriculture, medical applications, and consumer goods. Recent advancements in biopolymer technology have led to the creation of various types of plant-derived plastics, including polylactic acid (PLA), polyhydroxyalkanoates (PHA), starch-based bioplastics, bio-polyethylene (bio-PE), and cellulose-based plastics. These materials exhibit improved biodegradability, reduced environmental toxicity, and enhanced functionality across industries. Despite their potential, the commercialization of plant-based bioplastics faces several hurdles. One of the major concerns is their high production cost, which makes them less competitive compared to petroleum-based plastics. Additionally, certain bioplastics require specific industrial composting conditions for degradation, making their disposal challenging in regions lacking proper composting infrastructure. The mechanical and thermal properties of some bioplastics also present challenges, as they may be less durable, heat-resistant, and water-resistant compared to synthetic polymers. Furthermore, concerns have been raised regarding the sustainability of large-scale production, as the cultivation of raw materials such as corn and sugarcane competes with food production, raising ethical and resource management issues. This paper explores the chemical composition, material properties, and production methods of plant-based bioplastics, along with their environmental benefits and industrial applications. It also discusses the challenges associated with their large-scale implementation and the regulatory frameworks that govern their production and disposal. Additionally, strategies for improving their cost-effectiveness, mechanical strength, and compostability are examined. With the growing emphasis on environmental conservation, circular economy practices, and sustainable manufacturing, plant-based bioplastics hold great promise in reducing plastic pollution and transitioning toward a more sustainable future. As industries and governments seek to mitigate the environmental impact of plastic waste, the adoption of bioplastics could serve as a crucial step in achieving global sustainability goals.